Evaluation of the effects of onboard sorting and experimental holding practices on the post-catch survival of brown shrimp (Crangon crangon L.). Issue 7 (9th August 2018) - Vermeersch, Xavier H. C.; Chiers, Koen; Decostere, Annemie; Van Weyenberg, Stephanie; Vlaemynck, Geertrui
ABSTRACT: European brown shrimp ( Crangon crangon ) have great commercial value. Recently, an increasing demand for fresh shrimp has led fishermen to land part of their catch alive. In the present study, the effects of various parameters on the post-catch survival of brown shrimp were investigated by housing them in natural seawater and monitoring survival for two weeks. In a first experiment shrimp survival was tested under high population densities at different temperature settings ranging between 8°C and 21°C. A second experiment investigated the effect of a sand layer in the holding tanks when shrimp were housed at low population densities. Finally, the impact of onboard sorting with a rotary sorting riddle on subsequent survival was assessed. A higher survival rate was found at lower water temperatures. The use of a sand substrate did not significantly improve survival but did result in a more even distribution of shrimp across the bottom of the holding tanks. Onboard sorting with a mechanical rotary sorting riddle did not significantly affect the survival of brown shrimp during the first four days of holding although injuries sustained during onboard handling resulted in high mortality at the time of landing.